PENERAPAN STRATEGI PEMBELAJARAN STAD BERBANTUAN KAHOOT UNTUK MENINGKATKAN PENGUASAAN MUFRODAT PADA SISWA KELAS VII MTS - Andreano Eka Nur Fadillah; Yeni Lailatul Wahidah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Vocabulary mastery is a crucial component of Arabic language learning because it forms the foundation for comprehension, speaking, reading, and writing skills. Low vocabulary mastery and a lack of active student engagement motivated this study. The study aims to improve Arabic vocabulary mastery through the Student Teams Achievement Division (STAD) strategy, supported by Kahoot, among seventh-grade students at MTs Assyifa Karang Sari for the 2025/2026 academic year. The method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, encompassing the planning, implementation, observation, and reflection stages across two cycles. The research subjects were 28 seventh-grade students. Data were collected through observation, tests, and documentation, then analyzed quantitatively and qualitatively. The results showed a significant increase in student learning achievement, rising from 42.86% in the pre-cycle to 60.71% in Cycle I, and reaching 82.14% in Cycle II. Student activities also increased, making learning more active, interactive, and student-centered. The combination of the STAD strategy and Kahoot has proven effective in creating an enjoyable learning environment while improving vocabulary mastery. These findings contribute to providing an innovative learning alternative that Arabic teachers can implement to enhance vocabulary mastery and active student participation in the classroom. ABSTRAK Penguasaan mufrodat merupakan komponen krusial dalam pembelajaran Bahasa Arab karena menjadi fondasi kemampuan memahami, berbicara, membaca, dan menulis. Rendahnya penguasaan mufrodat serta kurangnya keterlibatan aktif siswa melatarbelakangi penelitian ini. Penelitian bertujuan meningkatkan penguasaan mufrodat Bahasa Arab melalui strategi Student Teams Achievement Division (STAD) berbantuan media Kahoot pada siswa kelas VII MTs Assyifa Karang Sari Tahun Ajaran 2025/2026. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart, mencakup tahap perencanaan, pelaksanaan, observasi, dan refleksi dalam dua siklus. Subjek penelitian adalah 28 siswa kelas VII. Data dikumpulkan melalui observasi, tes, dan dokumentasi, kemudian dianalisis secara kuantitatif dan kualitatif. Hasil penelitian menunjukkan peningkatan signifikan pada ketuntasan belajar siswa, yakni dari 42,86% pada pra-siklus menjadi 60,71% pada Siklus I, dan mencapai 82,14% pada Siklus II. Aktivitas siswa pun meningkat, menjadikan pembelajaran lebih aktif, interaktif, dan berpusat pada siswa. Kombinasi strategi STAD dan media Kahoot terbukti efektif dalam menciptakan suasana belajar yang menyenangkan sekaligus meningkatkan penguasaan mufrodat. Temuan ini berkontribusi dalam menyediakan alternatif pembelajaran inovatif yang dapat diimplementasikan oleh guru Bahasa Arab guna meningkatkan penguasaan mufrodat dan partisipasi aktif peserta didik di kelas.